FORMULATION AND PHYSICAL STABILITY EVALUATION OF ESSENTIAL OIL PARFUME - Yelfi Anwar; Efa Bonita; Andrianopsyah Mas Jaya Putra (Media Bina Ilmiah, 2023)
The need for essential oils will continue to increase by up to 8–10% in line with the increasing production of perfume. This shows that there is a public need for the perfume, which is increasing day by day. This research design is experimental and aims to determine a symptom or effect that arises as a result of certain treatments, to produce eau de toilette-type formulas and perfumes that have good quality and are liked by respondents. The evaluation was carried out using several tests, namely the organoleptic test, specific gravity test, fragrance resistance test, spreadability test, sensitivity test, physical stability test, pH test, and hedonic test. The results showed that organoleptically, all formulas produced a yellow color, were homogeneous and free of particles, and had a slightly pungent smell of fresh oranges. The specific gravity of all formulas met the requirements, with the largest specific gravity F2 of 0.86 at cold temperatures. The fragrance resistance test still smelled after 4 hours. The biggest spot test results were on F1, with a diameter of 49.17 mm. The sensitivity test did not show any allergic reactions or irritation of the skin during the use of the perfume, and the physical stability test of the entire formula did not show any separation or change in shape over a period of 7 weeks, both in room temperature storage and at cold temperatures. The entire formula has a liquid texture, is not sticky, and is easy to apply. The results of the evaluation of pH testing are in the range of 5–6 and have fulfilled the requirements of SNI 16-4399-1996, cosmetic preparations must have a pH according to the pH of the skin, which is in the range of 4.5–6.5. And the most preferred formula is Formula 1.